Assessment of genetic diversity among Ixora genotypes through morphological and RAPD molecular marker analysis - Akilan P; Visalakshi M; Manikanda Boopathi N; Sathiyamurthy V A; Vanitha K (Plant Science Today, 2024)
Ixora a genus in the Rubiaceae family commonly known as jungle geranium, was the focus of the study. However, classifying Ixora species has been challenging due to environmental influences on phenotypic traits. This study explores the genetic diversity and morphological traits of 11 Ixora genotypes from various regions in India using 15 RAPD markers and morphological assessments. A total of 210 bands were generated, Unweighted Pair Group Method for Arithmetic Average (UPGMA) Cluster analysis revealed significant genetic relationships among the genotypes. Notably, Genotypes 9, 10 and 11 shared similar banding patterns with marker OPF 02, while Genotypes 4 and 7, despite differing growth habits, showed close genetic ties and shared RAPD markers OPA03 and OPE04. A unique marker (OPA03 - 340 bp) was identified exclusively in Genotype 4. Principal Component Analysis (PCA) indicated that 2 principal components explained 77.074 % of the total variance, highlighting plant height and leaf number as significant traits. Heat map clustering further illustrated phenotypic variability, grouping genotypes based on morphological similarities. This study demonstrates the utility of RAPD markers in distinguishing Ixora genotypes and provides valuable insights into morphological traits, guiding future breeding programs and genetic research.